2015
DOI: 10.15376/biores.10.4.7604-7617
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Dynamics of Biomass Residues in Hot-Stage

Abstract: Original data for mass, element, and methane dynamics under controlled pyrolysis are presented for several biomass feedstocks. The experimental system consisted of an environmental (low-vacuum) scanning electron microscopy (ESEM) with a hot-stage and energy-dispersive X-ray spectroscopy (EDS) detector. A tunable diode laser (TDL) was coupled to the ESEM vacuum pump to measure the methane partial pressure in the exhaust gases. Thermogravimetric analysis and differential thermal analysis (TG/DTA) in a N2 atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The biochars had similar properties to those reported by Bergier et al. (2015), with 7.8% ash, 2.1% K, and 0.3% P content. The results indicated that low applications of biochars increased the seedling survival rate and the overall measurements of plant development in the evaluated species.…”
Section: Applications Of Brazil Nut Wastes In the Literaturesupporting
confidence: 81%
See 2 more Smart Citations
“…The biochars had similar properties to those reported by Bergier et al. (2015), with 7.8% ash, 2.1% K, and 0.3% P content. The results indicated that low applications of biochars increased the seedling survival rate and the overall measurements of plant development in the evaluated species.…”
Section: Applications Of Brazil Nut Wastes In the Literaturesupporting
confidence: 81%
“…These results are associated with the content of lignin (Brazil nut > palm kernel > açai), which highly influences biochar yield (Demirbas, 2004). Bergier et al (2015) produced biochar from various natural feedstocks, including Brazil nut endocarp, and meso-and exocarp separately. The endocarp biochar yield was the highest at 300 • C, yielding around 82%.…”
Section: Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Some basic properties of PCB and CCB are listed in Table 7. The carbon content of PR is 81.79 wt %, which is much higher than 46.03 wt % carbon of the residue from high density polyethylene pyrolysis (Jamradloedluk and Lertsatitthanakorn, 2014) and 60.3 wt % carbon of the residue from Candeia tree pyrolysis (Bergier et al, 2015). This confirmed that the PR from waste tires was a carbon-rich substance.…”
Section: Resultsmentioning
confidence: 90%
“…The results are consistent with those found in the literature. Bergier et al (2015) [17] and Gao et al (2016) [15], reported that the largest loss of mass was in the second stage, related to cellulose and hemicellulose, in an approximate temperature of 400°C and that the lignin, being more stable, degraded at a higher temperature. Table 11 shows that, in the first stage, where sample dehydration occurs, the pre-treatment with acetic acid had the largest mass loss, 9.01%.…”
Section:  Thermogravimetry and Differential Thermal Analysis (Tmentioning
confidence: 99%